Makanan Tradisional Kabupaten Lima Puluh Kota Dalam Food Photography - hydhayatul, putry; Masta, Putri Khairina; Emas, Cindi Adelia Putri (Matalensa: Journal of Photography and Media, 2024)
The traditional food of Lima Puluh Kota Regency as a form of traditional culinary culture needs to be re-actualized, namely by displaying it through visual images that are more attractive, refreshing and have a contemporary nuance through a work of food photography. In the culinary industry, food photography is an important requirement, both for commercial and non-commercial purposes. This is because artistic visual images can increase the image and selling value of the food displayed. In realizing this, several methods of creating work were carried out, namely qualitative descriptive methods with observation activities, literature studies and interviews. The data obtained was then analyzed qualitatively and presented descriptively. Then, the design method and work realization were carried out to realize the concept that had been designed, with the shooting process carried out indoors using a Cannon EOS 1200D camera and other supporting equipment. The creation of the work "Traditional Food of Lima Puluh Kota Regency in Food Photography" includes the food Sate Danguang-Danguang, Unja Ikan, Kipang Ompiang, and Galamai Boreh Rondang as photographic objects. From this food, 4 photo works were created and it is hoped that the creators can overcome the problem of preserving the traditional food of Lima Puluh Kota Regency, becoming one of the superior regional culinary and cultural products, and can increase the interest of local people and tourists in consuming traditional food, especially in the Lima Puluh Kota Regency.